The analysis of methylxanthine fractions obtained from Camellia sinensis cultivated in Turkey and effects on the in vitro inhibition of CYP2D6 enzyme - Attar, Azade; Altikatoglu Yapaoz, Melda (WILEY, 2023)
Tea is a worldwide consumed herbal beverage and it was aimed in this study to reveal the major fractions of green and black tea in order to enlighten the in vitro inhibition potency on the well-known drug metabolizing enzyme CYP2D6 activity. Methylxanthine fractions were extracted from green and black tea and a yield of 0.265 g (1.06%) for 25 g of dried black tea and 0.302 g (1.2%) for 25 g of green tea was calculated. High-performance liquid chromatography analysis represented that the major components of the methylxanthine fractions were caffeine, theobromine, and theophylline. Methylxanthine content of black tea was 368.25 +/- 4.6 mu g/ml caffeine, 89.30 +/- 2.3 mu g/ml theobromine, and 3.40 +/- 0.5 mu g/ml theophylline, whereas that of green tea was 176.50 +/- 3.7 mu g/ml caffeine, 53.85 +/- 1.4 mu g/ml theobromine, and 2.06 +/- 0.7 mu g/ml theophylline. The results of concentration-dependent inhibition studies were 76% green tea, 75% black tea, and 55% caffeine at concentration of 10 mg/ml. The inhibition rates of green and black tea on CYP2D6 activity were 76% and 75%, respectively, where that of quinidine, the well-known inhibitor of CYP2D6, was 82%. Our results indicate that green and black tea is very likely to modify the CYP2D6 enzyme activity.
Keywords: Black Sea tea; Camellia sinensis; in vitro inhibition; methylxanthines; CYP1A2; CYP3A4; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology